Organocatalytic asymmetric Michael addition between 3-subsituted oxindoles and enals catalyzed by camphor sulfonyl hydrazine. Issue 4 (10th January 2019) - Cheng, Wen-Fu; Chen, Ling-Yan; Xu, Fang-Fang; Lin, Wei-Yu; Ren, Xinfeng; Li, Ya
Abstract : 3, 3-Disubstituted oxindoles containing vicinal stereogenic carbon centers have been synthesized through organocatalytic asymmetric Michael addition between 3-substituted oxindoles and enals catalyzed by chiral camphor sulfonyl hydrazines (CaSHs). Abstract : Organocatalytic asymmetric Michael addition between 3-substituted oxindoles and enals catalyzed by chiral camphor sulfonyl hydrazines (CaSHs) has been developed. A wide range of 3-substituted oxindoles and enals were successfully used, giving the corresponding 3, 3-disubstituted oxindoles containing vicinal stereogenic carbon centers in good yields with good to excellent enantioselectivities and moderate to good diastereoselectivities (up to 89% yield, 99% ee and 99 : 1 dr).